PENGEMBANGAN KONSEP DAN PEMBAHARUAN SISTEM BOOKING ORDER BERBASIS ODOO DI PT. HASHMICRO SOLUSI INDONESIA - I Putu Agus Arya Wiguna; I Gusti Ngurah Anom Cahyadi Putra; Ida Bagus Gede Dwidasmara (Jurnal Pengabdian Informatika, 2024)
The problems commonly encountered by users in a booking order system are often related to the use of a complex or non-intuitive interface, which can result in a poor user experience. Difficulties in navigating the system, filling out order forms, or identifying the appropriate options can lead to high order cancellations and conversion failures. Furthermore, a major issue is inaccurate availability. When the system is not updated in real-time or fails to synchronize with the actual inventory, there is a risk of accepting orders when the product stock is already depleted. To address these issues, it is proposed to design a website based on Odoo for creating the booking order system. Odoo is designed with an intuitive and easily understandable user interface. Additionally, an Odoo-based website is supported by a powerful inventory module, allowing efficient management and tracking of existing inventory, as well as accurate management of product deliveries to avoid inventory shortages or overstocking.